A Remotely Delivered Progressive Walking Intervention for Adults With Persistent Symptoms of a Mild Traumatic Brain Injury: Feasibility and Exploration of Its Impact - Alarie, Christophe; Gagnon, Isabelle; Guise, Elaine de; McKerral, Michelle; Kersalé, Marietta; Hoog, Béatrice van het; Swaine, Bonnie (Frontiers in Rehabilitation Sciences, 2022)
Introduction Persistent post-concussion symptoms following a mild traumatic brain injury (mTBI) can impact function and participation of adults. Physical activity is recommended to reduce symptoms and foster return to normal activities. Adults with a mTBI may have personal factors or experience accessibility issues restricting physical activity. Walking is a physical activity accessible to most that could be delivered remotely. Objectives Determine the feasibility, safety, and acceptability of a remotely delivered progressive walking intervention designed for adults with persistent mTBI symptoms and explore its effects on health-related outcomes. Methodology This feasibility study using a single-group pre-post mixed methods convergent parallel design was conducted remotely. Adults aged 18–65 years with a mTBI reporting persistent symptoms for ≥3 months were recruited. The 8-week remote progressive walking intervention aimed to increase the weekly number of steps walked by 40% based on a 1-week baseline measured by a Fitbit Inspire 2 activity monitor. Feasibility measures were about the intervention, its remote delivery, safety, and acceptability. Health-related outcomes were post-concussion symptoms, kinesiophobia, mood, sleep, fatigue, and quality of life. Semi-structured exit interviews were recorded and transcribed verbatim. Quantitative and qualitative data were analyzed separately, and results merged, compared, and contrasted. Descriptive statistics and paired samples t-tests were used. The qualitative analyses followed an iterative content analysis approach using reflexivity and triangulation of sources. Results Twenty adults (16 women) aged 42.5 ± 11.51 years with persisting symptoms for 9.25 ± 6.43 months participated, adhered to 94.38% of sessions, completed the intervention, and found it to be feasible, safe and acceptable. Participants increased weekly total number of steps walked (change = 14,886 ± 18,283; t = 3.55, p = 0.002). Severity of post-concussion symptoms (change = −6.42 ± 10.69; t = −2.62, p = 0.018), kinesiophobia (change = −5 ± 6.86; t = 3.18, p = 0.005), anxiety (change = −1.53 ± 3.01; t = −2.21, p = 0.04), and fatigue (change = −10.21 ± 10.20; t = −4.37, p < 0.001) were reduced, whilst quality of life improved (change = 10.58 ± 13.35; t = 3.46, p = 0.003). Participants' perceptions corroborate most quantitative results; they felt improved self-efficacy about physical activity and provided five key recommendations. Discussion This study demonstrates the feasibility, safety, and acceptability of the remote 8-week progressive walking intervention, a promising approach to reduce persisting symptoms, improve physical activity level health-related outcomes and quality of life of adults with persistent post-concussion symptoms following a mTBI.